A Case of Relapsing Kikuchi-Fujimoto Disease - Talayeh Rezayat; Matthew B. Carroll; Bryan C. Ramsey; Andria Smith (Case Reports in Otolaryngology)
Kikuchi-Fujimoto disease (KFD) or histiocytic necrotizing lymphadenitis was first described in Japan in 1972. It is described as a benign syndrome most commonly involving cervical lymphadenopathy, fever, and night sweats. The etiology of KFD is unknown but it is thought to be triggered by an autoimmune or viral process with an exaggerated T-cell-mediated immune response. KFD can mimic other serious conditions such as lymphoma, systemic lupus erythematosus (SLE), herpes simplex, and Epstein Barr virus. Diagnosis is confirmed histopathologically. Kikuchi’s disease is typically reported to have a self-limiting course, resolving within several months and with a low recurrence rate between 3% and 4%. There is no specific treatment for KFD but any treatment is generally directed towards symptomatic relief with antipyretics and anti-inflammatory medications. In severe cases corticosteroids have been used. Here we describe a case of a previously healthy 26-year-old female that presented with fever and cervical lymphadenopathy. Malignancy and infections were ruled, and she was diagnosed with KFD histopathologically by lymph node biopsy. Her case is a severe case of KFD that despite treatment with multiple courses of corticosteroids and an immune modulating agent, relapsed.